The development of real-time rendering for large-scale 3D virtual heritage - Sunar, Mohd. Shahrizal; Daman, Daut; Bade, Abdullah; Mohd. Shuaib, Norhaida; Shamsudin, Hasnul Hadi; Mohd. Arif, Nor Azhar (Faculty of Computer Science and Information System, 2008)
Today's computing technology has been able to create a complex 3D environment for the development of interactive graphical applications such as computer games and simulations. Geometric models in this 3D environment consist of thousands and even millions of polygons. This causes the graphics hardware system to experience difficulty rendering the entire model formed by a large number of polygons at a good interactive rate. Indirectly the cost of computation and processing time for each polygon for geometric objects also increases. The main goal of this research is to develop techniques to reduce the cost of computing for a large-scale Virtual Heritage System (SWM) environment. At the same time SWM can maintain the complexity of the 3D environment. This is intended to enable SWMs that are usually only feasible on high-performance computer systems in order to be implemented using lower-powered computer systems. Overall, this research has succeeded in generating new techniques for real-time display generation for SWM. These techniques are virtual environment management techniques, level-of-detail (LOD) techniques, culling portal techniques, and environmental detection techniques. The techniques produced are based on analysis of techniques for the optimization of memory space usage. The development of this project indirectly achieves the goal of overcoming the problem of computing costs and managing 3D objects in a complex virtual search system efficiently.